249 HIGH MORTALITY RATES FOR PREMATURE INFANTS WITH PROSTAGLANDIN-DEPENDENT CONGENITAL HEART DISEASE. Issue 1 (1st January 2007) - Job, L.; Ninnis, J.; Wan, K.; Deming, D.
Abstract : Background: Using prostaglandin (PGE1) infusion to stabilize circulation prior to corrective surgery is standard of care for term infants with severe congenital heart disease (CHD). There is limited information on PGE1 therapy and outcomes for low birth weight (LBW) infants with CHD. Objective: To study mortality rates for LBW infants with complex CHD requiring PGE1 infusion as a bridge to surgery. Methods: We reviewed 5 years of our experience with infants < 2, 500 g birth weight (BW) requiring PGE1. Results: Forty-three infants < 2, 500 g at birth were started on PGE1 infusion and referred to us for possible CHD. Nine infants had structurally normal hearts and were excluded from further analysis. Twenty-two of the remaining 34 infants died, for an overall mortality rate of 65%. Six infants (two survivors and four who died) were term but small for gestational age. The BW-specific mortality rates are in the Table . Median (range) BW of the entire group was 1, 720 (552-2, 474) g and GA 34 (26-40) weeks. There were 18/34 (53%) infants in the total group who had recognized syndromes: 7 (20%) had trisomies (1 T-21 who survived, 2 T-13, and 4 T-18); 3 additional infants had lethal syndromes. Of the 9 infants identified as having lethal syndromes, median length of stay (LOS) was 5 (1-12) days; in contrast to the 25 infants who were supported awaiting surgical repair, median LOS was 28 (0-319) days. Mortality rate for those without an identified lethal syndrome was 52%. There was decreasing mortality with increasing BW. Conclusion: We found a high rate of mortality and syndromes among infants < 2, 500 g BW referred for PGE1-dependent CHD. In our experience, the prognosis for infants < 1, 000 g on long-term prostaglandins awaiting surgical repair was dismal. These data lend support to consideration for earlier surgical intervention in premature infants with complex congenital heart disease.